SYSTEMATIC ASSESSMENT OF ECONOMIC SECURITY OF ENTERPRISES AT NETWORK STRUCTURES: MAIN INDICATORS AND METHODS OF IMPLEMENTATION - SHATARSKYI, ARTUR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the current conditions of turbulence of economic processes in the field of network enterprises, valuation technologies are a powerful means of forming the effective functioning of economic entities aimed at maximizing profits and harmonizing relations between stakeholders. Please note that the enterprises of network structures depend on the state of economic security of the country. Meanwhile, it should be noted that currently the economic security of Ukraine is under threat, as all components of economic security are in danger. Problems of own economic security arise before each network structure not only in times of crisis, but also during work in the stable economic environment, the complex of the solved tasks at the same time has essential difference. The article examines the substantive characteristics of the concept economic security, as well as substantiates the methodological approaches to assessing the economic security of enterprises at network structures. A comprehensive study of the limit values of determinants in the system of economic security at network structures with the separation of indicators the state: stable, pre-crisis, crisis, critical. The peculiarities of the main approaches to ensuring the economic security of enterprises at network structures, in particular indicator, economic-mathematical, resource-functional, are substantiated.